Application of the Educational Game to Enhance Student Learning - Cheung, Siu Yin; Ng, Kai Yin (Frontiers in Education, 2021)
ABSTRACT: The purpose of this study is to investigate the use of an educational game to enhance student learning effectiveness. This study consisted of 56 college students majoring in physical education and recreation management (32 men, 24 women, age M=21years, SD=1.72). Students used the educational computer game “PaGamO” to study the motor learning and development course. Students received rewards based on their individual and group “PaGamO” scores. Regression analysis indicated that “PaGamO” score was a significant (p < 0.01) predictor of multiple choice (MC) score in the final examination, there was a medium positive correlation (β = .354). The R2 suggests that 12.6% of MC score was explained by “PaGamO” score. Quantitative and qualitative mixed-method approach was used to gain insights into students’ perceptions and experiences of the educational game. The top three statements of a modified questionnaire from Riemer and Schrader (2015) are: (1) “In my opinion, the use of “PaGamO” enables me to better prepare for the final examination” (M=5.04, SD=1.41), (2) “In my opinion, the use of “PaGamO” enables me to understand learning contents” (M=4.8, SD=1.19), (3) “In my opinion, the use of “PaGamO” allows me to apply knowledge” (M=4.75, SD=1.08). The top three motives to play “PaGamO” were “fun”, “self-learning”, and “want to get a higher grade in the final examination”. By using gamification as a tool for learning and studying, students did find "PaGamO" effective for their learning experience. Both intrinsic and extrinsic participation motives are reasons why students play "PaGamO". Furthermore, due to its convenience, using mobile devices to play "PaGamO" is more popular than using computers and tablet devices. In conclusion, the combination of gamification and traditional learning methods can enhance students' learning outcomes.